Peran Pengawasan Komisi IX DPR RI Dalam Kebijakan Jaminan Sosial Pekerja Migran Indonesia - Nabila Udzrotu Shauma; Septi Dwi Wulandari; Nadia Putri; Mawar Mawar (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
Indonesian Migrant Workers are every Indonesian citizen who will, are currently, or have done work for wages outside the territory of the Republic of Indonesia, this study was conducted to analyze and determine the role of Supervision of Commission IX of the House of Representatives of the Republic of Indonesia in the Social Security Policy of Indonesian Migrant Workers. This research is a research study using literature which is analyzed from various existing references and processed research materials on the policy of migrant workers in Indonesia related to the authority of the DPR in the supervisory function. The supervisory role carried out by Commission IX of the DPR RI in this regard is quite good and significant in its achievement. However, it has not been said to be optimal, because the problems related to the governance of the implementation of social security for Indonesian migrant workers which were discussed by the Minister of Manpower in a working meeting with Commission IX of the DPR RI, have not been fully resolved in terms of supervision carried out by Commission IX of the DPR. RI.